اللغة العربية لأعراض خاصة من واقع تعليمي: جامعة أفريقيا العالمية و الجامعة الإسلامية العالمية = Arabic for specific purposes: International University of Africa University and International Islamic University Malaysia: educational reality - Mohamed Osman, Abdoun; Hassan, Fekri Abidin; Ahmad, Nordin (2014)
The teaching of the Arabic language for the specific purposes goes back to 2nd World War, but it found great interest in the modern era across different centers and institutions of public and higher education. It became part of the Applied Linguistics of the goals, specific approaches and entrances which are strongly connected to purposes and the needs of the students or learners. It is this paper to refer to the concept of special purpose statement and the difference between it and the general purpose, and the most important characteristics and features of each. And take this paper programs International University of Africa, and the International Islamic University as a model for this study, and shed light on the objectives, programs and the entrances of the two universities, in the context of the primary objective of the programs teaching Arabic language for special purposes, and access to the common denominators of the reality of the two universities, and how it relates to the concepts and methods of teaching Arabic Special Purpose.